Sediment biogeochemistry and diatom assemblages in dated sediment core from lake Teremendo (Michoacán, Mexico) - Marttiina V Rantala; Isabel Israde-Alcántara; Reza Safaierad; Wojciech Tylmann; Gilles Lepoint; Pierre Francus; John P Smol; Carsten Meyer-Jacob; Christopher Grooms; Nadine Mattielli; Sarah Metcalfe; Paweł Etmański; et al. (PANGAEA, 2025)
This dataset comprises multiproxy biogeochemical data and diatom assemblage data for a sediment sequence (LTe22-1) from lake Teremendo (Michoacán, Mexico). The data were used to explore connections between lake carbon cycling and related ecosystem processes under natural and anthropogenic environmental change over the past four centuries. The sediment core (155 cm in length) was retrieved with a Uwitec corer near the middle of the lake basin (water depth ~8 m) in April 2022. After initial core scanning, the sediment core was sectioned at 5-mm intervals. The data are provided for these discrete sediment sections from 0 cm down to the depth of 46.5 cm, covering a time period from 2022 to around 1650. Age estimates for each sediment section have been calculated based on radiolead (Pb-210) dating of the surface sediment sections and four radiocarbon (C-14) measurements. Diatom data include taxa present with at least 0.5% relative abundance in any sample.
In: Rantala, MV et al. (2025): Four centuries of multiproxy biogeochemical and diatom assemblage data in the sediments of lakes Santa Maria del Oro and Teremendo, central Mexico [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.972744